Corrective Feedback on Pronunciation Errors: Teacher’s Perception and EFL High School Students’ Self-Reflection - Neng Eva Agustuna; Rina Herlina; Didih Faridah (Universitas Bengkulu, 2019)
This research investigates EFL high school students’ self reflection of teacher’s corrective feedback on pronunciation errors. The methodology of this research was qualitative which used case study as a research design. The data were collected from classroom observation, semi-structured interview of one English teacher, and questionnaire of twenty five students at eleventh grade. The findings revealed that the students’ self reflection could be seen when the teacher providing the corrective feedback. The students could be aware that they often do the errors in pronouncing English because of the difficulties of using English. However, the teacher’s feedback was directed the students to learn about how to pronounce English properly. The researchers conclude that by using self-reflection, the students would be aware of their strength and weakness. Furthemore, it supports self motivated, self-awareness, self-observation, self-analysis, and self-evaluation of the students in pronouncing English. Finally, the researchers suggest that self-reflection can integrate into the other aspects such as writing, reading, and listening. Thus, the students can get the valuable learning process.